The Use of Instagram to Improve English Literature Students’ Self-Confidence in Mastering Speaking Skill - Aries Utomo; Islamiah Bastiar (IKIP PGRI Bojonegoro, 2020)
Abstract: Instagram is one of social media applications used in daily life now. It is used to uploading any picture, video, and live event. This research aims to describe the use of Instagram to improve English literature students’ self confidence in mastering speaking skill. This research was qualitative research. 28 students of the first semester in English Literature Department, Faculty of Culture Sciences, Mulawarman University were taken as respondents of this research. Technique of collecting data used was (1) interview, (2) observation, (3) questionnaire, and (4) documentation. Meanwhile, technique of analyzing data used was miles and Huberman’s model. Based on the research findings, it shows that (1) most of students strongly agree about the use of Instagram in mastering speaking skill and (2) students’ self-confidence in speaking skill can be improved. From those explanations, it can be concluded that Instagram can improve students’ speaking skill from inside to outside. Moreover, speaking through Instagram is more comfortable for passive students in the classroom. Besides that, students are more confidence to speak English than before through Instagram. Abstrak: Instagram adalah salah satu aplikasi media sosial yang digunakan dalam kehidupan sehari-hari sekarang. Ini digunakan untuk mengunggah gambar, video, dan acara langsung. Penelitian ini bertujuan untuk mendeskripsikan penggunaan Instagram untuk meningkatkan kepercayaan diri mahasiswa sastra Inggris dalam menguasai kemampuan berbicara. Penelitian ini adalah penelitian kualitatif. 28 siswa semester pertama di Jurusan Sastra Inggris, Fakultas Ilmu Budaya, Universitas Mulawarman diambil sebagai responden dari penelitian ini. Teknik pengumpulan data yang digunakan adalah (1) wawancara, (2) observasi, (3) kuesioner, dan (4) dokumentasi. Sementara itu, teknik analisis data yang digunakan adalah mil dan model Huberman. Berdasarkan temuan penelitian, itu menunjukkan bahwa (1) sebagian besar siswa sangat setuju tentang penggunaan Instagram dalam menguasai keterampilan berbicara dan (2) kepercayaan diri siswa dalam keterampilan berbicara dapat ditingkatkan. Dari penjelasan tersebut, dapat disimpulkan bahwa Instagram dapat meningkatkan keterampilan berbicara siswa dari dalam ke luar. Selain itu, berbicara melalui video Instagram lebih nyaman bagi siswa pasif di kelas. Selain itu, siswa lebih percaya diri untuk berbicara bahasa Inggris daripada sebelumnya melalui Instagram.